Pidgins, Creoles and mixed languages : an introduction - Velupillai, Viveka, 1974- (Creole language library, 2015)
"This lucid and theory-neutral introduction to the study of pidgins, creoles and mixed languages covers both theoretical and empirical issues pertinent to the field of contact linguistics. Part I presents the theoretical background, with chapters devoted to the definition of terms, the sociohistorical settings, theories on the genesis of pidgins and creoles, as well as discussions on language variation and the sociology of language. Part II empirically tests assumptions made about the linguistic characteristics of pidgins and creoles by systematically comparing them with other natural languages in all linguistic domains. This is the first introduction that consistently applies the findings of the Atlas of Pidgin and Creole Language Structures and systematically includes extended pidgins and mixed languages in the discussion of each linguistic feature. The book is designed for students of courses with a focus on pidgins, creoles and mixed languages, as well as typologically oriented courses on contact linguistics"--Provided by publisher.